Kad Hari Raya - Al-Yafii, Kamal; Amiruldin, Faizah; Kamal, Alan; Kamal, Alwizah; Kamal, Sabri; Kamal, Amirah; Kamal, Alia
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada Kamal Al-Yafii, Faizah Amiruldin, Alan, Alwizah, Sabri, Amirah & Alia